2080. Impact of the Implementation of a Rapid Meningitis/Encephalitis Multiplex Polymerase Chain Reaction Panel on Clinical Outcomes: Multicenter, Retrospective Cohort of Adult and Pediatric Patients. (26th November 2018) - Evans, Martha; Rose, Dusten; Merkel, Kathryn
Abstract: Background: Meningoencephalitis has a high mortality rate, therefore rapid identification of the underlying etiology is essential to optimize clinical and stewardship outcomes. The standard for diagnosis of meningoencephalitis included cerebrospinal fluid (CSF) culture and viral polymerase chain reaction (PCR) until approval of the BioFire ® Meningitis/Encephalitis (ME) panel, a multiplex PCR panel for the rapid detection of 14 central nervous system pathogens. The objective of this study was to determine the impact on clinical outcomes of the newly adopted ME panel in a central laboratory as compared with previously utilized CSF studies within a large, multicenter health system Methods: This is a multicenter, retrospective cohort study of adult and pediatric patients who received at least one dose of intravenous (IV) acyclovir for presumed meningoencephalitis, with study patients divided into pre-ME and post-ME panel cohorts. The primary endpoint is duration of IV acyclovir. Secondary endpoints include duration of antibacterials, in-hospital mortality, intensive care unit length of stay (LOS), hospital LOS, rates of acute kidney injury and test-turnaround time (TAT). Subgroup analyses were performed analyzing the impact of number of daily couriers and distance from the central laboratory on TAT. Results: A total of 208 patients were included: 87 pediatric and 121 adult. The duration of IV acyclovir decreased after implementation of the ME panel (41.6 vs. 30.8 hours; P < 0.01). The TAT was reduced with the implementation of the ME panel (37.3 vs. 6.2 hours; P < 0.01). There were no significant differences in the remaining secondary outcomes. Subgroup analyses of the post-ME cohort showed that the number of daily couriers to the central laboratory and the distance from the central laboratory significantly impacted TAT ( P < 0.01) but not duration of IV acyclovir. Conclusion: The ME panel significantly reduced the duration of IV acyclovir and TAT, which could have cost and safety implications when applied to a larger patient population. Multicenter healthcare systems implementing the ME panel may consider on-site ME platforms at multiple sites due to the significant effect of a central laboratory on TAT. Disclosures: All authors: No reported disclosures.